2001
DOI: 10.1038/86019
|View full text |Cite
|
Sign up to set email alerts
|

Cdk5 is involved in neuregulin-induced AChR expression at the neuromuscular junction

Abstract: Here we describe an important involvement of Cdk5/p35 in regulating the gene expression of acetylcholine receptor (AChR) at the neuromuscular synapse. Cdk5 and p35 were prominently expressed in embryonic muscle, and concentrated at the neuromuscular junction in adulthood. Neuregulin increased the p35-associated Cdk5 kinase activity in the membrane fraction of cultured C2C12 myotubes. Co-immunoprecipitation studies revealed the association between Cdk5, p35 and ErbB receptors in muscle and cultured myotubes. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
145
2
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(157 citation statements)
references
References 43 publications
8
145
2
2
Order By: Relevance
“…Cdk5 and p35 have recently also been shown to regulate presynaptic and postsynaptic activity by phosphorylating Munc-18, amphiphysin, and the NR2A subunit of the N-methyl-D-aspartate receptor (7)(8)(9)(10)(11). Cdk5 activity also regulates dopamine signaling by phosphorylating DARPP-32 protein (12) and has been shown to up-regulate the expression of acetylcholine receptor at the neuromuscular junction (13). These studies indicate that Cdk5 is a multifunctional protein kinase in the central nervous system.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Cdk5 and p35 have recently also been shown to regulate presynaptic and postsynaptic activity by phosphorylating Munc-18, amphiphysin, and the NR2A subunit of the N-methyl-D-aspartate receptor (7)(8)(9)(10)(11). Cdk5 activity also regulates dopamine signaling by phosphorylating DARPP-32 protein (12) and has been shown to up-regulate the expression of acetylcholine receptor at the neuromuscular junction (13). These studies indicate that Cdk5 is a multifunctional protein kinase in the central nervous system.…”
mentioning
confidence: 75%
“…To determine the target substrate for Cdk5, we based our analysis on the observation that the Cdk5-p35 complex is implicated in neuregulininduced acetylcholine receptor expression at the neuromuscular junction (13). This suggested that ErbB receptors might be a substrate for Cdk5 phosphorylation.…”
Section: Reduced Brain Lipid Phosphorylation and Pi3k Activity Inmentioning
confidence: 99%
See 1 more Smart Citation
“…26 The mysterious nuclear and nucleolar activities of ERBB3 76,78,79 must be unraveled. Further study is needed of the involvement of non-NRG, non-ERBB regulators of ERBB3, such as CDK5, [122][123][124] BRK, 125 SRC, 126 and MET. 120 The fascinating and widely expressed ERBB3 effector EBP1 has thus far been examined mainly in mammary and prostate cells; [154][155][156][157][158][159][160][161][162][163][164] may it be important also in other cancers where ERBB3 is clearly a player, such as lung and melanoma?…”
Section: Discussionmentioning
confidence: 99%
“…123 Furthermore Cdk5 and Erbb3 coimmunoprecipitated, and Cdk5 caused ser/thr phosphorylation on immunoprecipitated Erbb3. These results for muscle were confirmed in Cdk5 −/− knockout mice.…”
Section: Erbb3 Interacting Proteins: Activation Signaling and Regulamentioning
confidence: 94%